2015
DOI: 10.1097/phm.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Comparison of Sprint Cycling Performance and Neuromuscular Characteristics in Able-Bodied Athletes and Paralympic Athletes with Cerebral Palsy

Abstract: The similarity in fatigue between the CP and AB groups indicates that elite athletes with CP may have a different exercise response to others with CP. The authors propose that this may result from high-level training over many years. This has rehabilitative implications, as it indicates near-maximal adaptation of the CP body toward normal levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 21 publications
3
38
1
Order By: Relevance
“…This raises the question; Can participation-focused interventions, that are highly engaging for children over sustained time periods [36], contribute to improvements in impairments and activity limitations? Emerging evidence suggests that long-term involvement in exercise may improve neuromuscular characteristics and functional capacity of people with cerebral palsy [37]. In typically developing children, those who regularly participated in sport over three years displayed better motor outcomes than children who only partially participated, or did not participate in sport at all [38].…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question; Can participation-focused interventions, that are highly engaging for children over sustained time periods [36], contribute to improvements in impairments and activity limitations? Emerging evidence suggests that long-term involvement in exercise may improve neuromuscular characteristics and functional capacity of people with cerebral palsy [37]. In typically developing children, those who regularly participated in sport over three years displayed better motor outcomes than children who only partially participated, or did not participate in sport at all [38].…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that individuals with CP display a reduced decline in force output over time during repeated maximal isokinetic muscle contractions (Stackhouse et al, 2005;Moreau et al, 2008Moreau et al, , 2009. However, in studies using elite Paralympic athletes with CP, we have recently shown that fatigue resistance may not be present in all individuals with CP (Runciman et al, 2015a). Indeed, we demonstrated that athletes with CP fatigue at a similar rate to able-bodied athletes in both supramaximal cycling trials (Runciman et al, 2015a) and running trials following the induction of fatigue (Runciman et al, 2015b).…”
mentioning
confidence: 61%
“…However, our previous research (using externally paced maximal trials) has shown that adult athletes with CP display similar levels of fatigue to AB athletes (Runciman et al., 2015a,b). The athlete sample, which is the same group of athletes used in the present study, comprised elite Paralympic athletes who were more closely matched in sprint performance to elite Olympic field hockey players.…”
Section: Discussionmentioning
confidence: 87%
“…Studies on children and adolescents with CP have confirmed differences in voluntary muscle activation, anaerobic performance, and agility [40]. A recent study of sprint cycling performance comparing Paralympic athletes to performance-matched, ablebodied athletes showed decreased power output in athletes with CP but statistically similar measurements of fatigue, suggesting that elite athletes with CP can improve sports performance and overcome deficits in neuromuscular activation through training [37]. Eccentric strength training has been studied as one particular regimen to promote neuromuscular adaptation in children and adolescents with CP, however this has not been studied in relation to sports performance [41].…”
Section: Athletes With Cerebral Palsy or Central Neurologic Injurymentioning
confidence: 96%
“…Prior literature has suggested that athletes with CP across sports activities commonly experience muscles strains and soft tissue injuries to a wide variety of anatomic regions that may be secondary to muscle imbalance caused by spasticity [12]. While increased muscle tone or spasticity may limit overall force production and range of motion around joints, it may also contribute to enhanced joint stability [36,37]. Of interest, medical treatments commonly used for spasticity, such as botulinum toxin and oral antispasticity medications, may have the potential to either improve or inhibit sports performance given their propensity to reduce tone while concomitantly increasing muscle weakness [38,39].…”
Section: Athletes With Cerebral Palsy or Central Neurologic Injurymentioning
confidence: 99%